Estimated variance components and breeding values for pre-weaning growth criteria in Romney sheep - Eslam Faid-Allah; E. Ghoneim; A.H.M. Ibrahim (Jurnal Ilmu Ternak dan Veteriner, 2016)
This study was carried out to investigate variance components, direct heritability, maternal genetic parameters, estimated breeding values and factors affecting pre-weaning growth criteria of Romney sheep. Data were collected over the period from 2006 to 2012 with records of 4989 lambs descended from 76 rams and 2190 ewes of Romney sheep maintained at S. Island of New Zealand via Gene Marker Lab., Faculty of Agric. and Life Sci., Lincoln Univ., New Zealand. Results proved that genetic and non-genetic factors affecting studied criteria had significant effects (P<0.05). Genetic and environmental estimates of live body weights at birth (LBW), weaning (LWW) and Kleiber ratio (KR) were 0.20±0.074, 0.15±0.042 and 0.14±0.052 for direct heritability (h2a±SE); 0.59±0.219, 0.41±0.023 and 0.08±0.002 for maternal heritability (h2m±SE); 0.11684, 2.6378 and 0.27565 for additive variances (σ2a), 0.34596, 7.1179 and 0.14532 for maternal variances (σ2m); and 0.002395, 10.1262 and 0.509339 for permanent environmental variances (σ2e), respectively. EBV’s of LBW, LWW and KR ranged from -0.555: 0.502, -1.554: 3.006 and -0.633: 0.242 direct, -0.863: 0.954, -4.942: 2.554 and -0.469: 0.179 maternal for rams, respectively; and -0.664: 0.830, -2.996: 4.586 and -1.651: 0.677 direct, 1.429: 1.142, -7.541: 4.920 and -1.223: 0.492 maternal for ewes, respectively. Results suggest the importance of considering the non-genetic factors in pre-weaning growth performance of lambs. Moderate heritability and positive coefficients of phenotypic and genetic correlation for studied criteria indicate to the possibility of improving them using traditional selection.